2012
DOI: 10.1017/s0950268812002695
|View full text |Cite
|
Sign up to set email alerts
|

Early high CMV seroprevalence in pregnant women from a population with a high rate of congenital infection

Abstract: Congenital cytomegalovirus (CMV) infection rates increase with maternal seroprevalence due to transmission from maternal non-primary infection. CMV seroprevalence estimates of pregnant women are needed for planning strategies against congenital CMV transmission. We aimed to determine the age-specific prevalence of serum antibodies for CMV in a representative age-stratified sample of unselected pregnant women from a Brazilian population. A total of 985 pregnant women, aged 12–46 years (median 24 years), were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
1
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 25 publications
7
24
1
2
Order By: Relevance
“…When women's origin was taken into consideration, seroprevalence among pregnant women of low socioeconomic level was 95%; among pregnant students, 69.9%, according to a cross-sectional study undertaken in Chile (37) . Those findings are similar to what is found in Brazil, where a study conducted with low-and medium-income pregnant women showed seroprevalence of 92.9% (10) . Controversially, a study among high-income pregnant women in Brazil showed a seroprevalence of 84% (38) .…”
Section: Epidemiologysupporting
confidence: 91%
See 1 more Smart Citation
“…When women's origin was taken into consideration, seroprevalence among pregnant women of low socioeconomic level was 95%; among pregnant students, 69.9%, according to a cross-sectional study undertaken in Chile (37) . Those findings are similar to what is found in Brazil, where a study conducted with low-and medium-income pregnant women showed seroprevalence of 92.9% (10) . Controversially, a study among high-income pregnant women in Brazil showed a seroprevalence of 84% (38) .…”
Section: Epidemiologysupporting
confidence: 91%
“…Whereas a non-primary infection shows a rate of vertical transmission of 1% (8) , a primary infection has a rate of 30%-40% (9) . CMV is a ubiquitous virus and its infection occurs mainly in childhood in most populations (10) . Its seroprevalence among women in reproductive age varies according to country and other epidemiological factors, with rates ranging from 40% (11,12) in developed countries to over 90% (10,13,14) in developing countries.…”
mentioning
confidence: 99%
“…The present study shows a high CMV IgG overall seroprevalence (92.1%), with no significant differences between rate in women with BOH and that with normal pregnancy. Thus the susceptibility rate in our study population was 7.9%, which was higher to that reported recently for Turkey [11], [17]- [22], Nigeria [23], [24], Brazil [25], Iran [26], [27], Bangladesh [28], Korea [29], and Cuba [30]. However, our study susceptibility was lower than that reported for France [31], Nepal [32], India [13], [33], [34], Switzerland [35], Croatia [36], Malaysia [37], Iran [12], [38], Poland [39], Ireland [10], Russia [40], Taiwan [41], Germany [42], Azerbaijan [43], Bangladesh [44], and Brazil [45].…”
Section: Discussioncontrasting
confidence: 64%
“…The 65.6% seroprevalence found in pregnant women in Durango is similar to the 62.4%-66% seroprevalences reported in pregnant women in Poland [13], Japan [14], and Norway [15], and higher than the 49% seroprevalence in white British pregnant women in the United Kingdom [16] and a 42.3% seroprevalence in pregnant women in Germany [17]. In contrast, the seroprevalence found in pregnant women in Durango is lower than the 92.6%-100% seroprevalences reported in pregnant women in Iran [18], Palestine [19], Brazil [20], Turkey [21], Nigeria [22], and Cuba [23]. …”
Section: Discussionmentioning
confidence: 99%